2020
DOI: 10.4491/eer.2019.284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbon to nitrogen ratio on the performance and stability of aerobic granular sludge

Abstract: The purpose of this study was to assess the nutrient salts removal efficiency and stability of the aerobic granular sludge (AGS) by change in C/N (carbon to nitrogen) ratio. The laboratory-scale experiments were performed to analyze the removal efficiencies for organic matter and contents of nitrogen, MLSS, sludge volume index, and extracellular polymeric substances (EPS) under C/N ratio conditions of 5.0, 10.0, 15.0, and 20.0. The microorganisms were observed using optical microscope and the microbial communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 88 publications
4
15
1
Order By: Relevance
“…These results (Fig. 1a) are in agreement with Kim et al, 7 Kim and Ahn, 9 and Kocaturk and Erguder. 6 In a study conducted under anoxic-aerobic regime with acetic acid as the carbon source, Kocaturk and Erguder 6 reported COD removal efficiency of 63-79 % at ratios COD/N 1-7.5, efficiency of 76-90 % at COD/N 10, and at COD/N 20 and 30 the efficiency of COD removal of 94 % and 93 %, respectively.…”
Section: Cod/n Ratio and Removal Efficiency Of Cod And Nsupporting
confidence: 92%
See 3 more Smart Citations
“…These results (Fig. 1a) are in agreement with Kim et al, 7 Kim and Ahn, 9 and Kocaturk and Erguder. 6 In a study conducted under anoxic-aerobic regime with acetic acid as the carbon source, Kocaturk and Erguder 6 reported COD removal efficiency of 63-79 % at ratios COD/N 1-7.5, efficiency of 76-90 % at COD/N 10, and at COD/N 20 and 30 the efficiency of COD removal of 94 % and 93 %, respectively.…”
Section: Cod/n Ratio and Removal Efficiency Of Cod And Nsupporting
confidence: 92%
“…COD removal efficiencies of 78.9, 86.7, 92.7, and 95.9 % were recorded in exper-iments under aerobic regime with acetate as the carbon source, at ratios of COD/N 5, 10, 15, and 20. 7 However, in experiments with high MLSS concentration, such as 8 g MLSS l −1 , the high COD removal efficiency of 89.4-95.6 % was recorded at C/N ratio lower than 2. 27 Kim et al 7 showed that the microorganisms' diversity decreased with the increase in the COD/N ratio from 5 to 20, and the increase in COD/N ratio had a direct effect on the stability of aerobic granules.…”
Section: Cod/n Ratio and Removal Efficiency Of Cod And Nmentioning
confidence: 93%
See 2 more Smart Citations
“…The color depth was correlated with the soluble protein content and could be measured by a spectrophotometer under the wavelength of 500 nm. The soluble polysaccharide was measured using the phenol-vitriol colorimetry method (Kim et al 2020). Furfural and hydroxymethyl furfural could be generated by the dehydration of polysaccharide using concentrated sulfuric acid.…”
Section: Methodsmentioning
confidence: 99%